AN EXPERIMENTAL AND NUMERICAL INVESTIGATION INTO THE STRENGTH OF ADHESIVELY BONDED KENAF FIBRE-REINFORCED POLYMER TO STEEL DOUBLE STRAP JOINT INCORPORATING EGGSHELL POWDER-TOUGHENED EPOXY ADHESIVE - YIP, CHIA LIA (2023)
Synthetic fibre-reinforced polymer (FRPs) has proven to be an excellent strengthening material in double strap joint (DSJ). Nevertheless, awareness of environmental pollution has increased the application of natural FRPs; however, limited research was found on strap material. Kenaf fibre-reinforced polymer (KFRP) has comparable specific strength with glass fibre-reinforced polymer (GFRP). Epoxy resin is widely used as a matrix of composites; however, it has low shear strength. Improvement of its properties is therefore required, for example, by incorporating biofiller such as eggshells from household waste, which contain calcite, into neat epoxy resin to improve its shear strength. This research aims to investigate the joint strength and associated response in adhesively bonded KFRP/steel DSJ. All the DSJ specimens underwent a two-stage approaches. In Stage 1, experimental work was performed on the specimens through quasi-static tensile tests, following ASTM D3528-96. In Stage 2, numerical studies were conducted to predict the strength using the extended finite element method (XFEM) within ABAQUS CAE. Subsequently, the strength prediction from developed 2-D FEA models was validated by the experimental datasets. Testing series includes variations of KFRP bond length, KFRP thickness and eggshell filler volume fractions. All testing specimens exhibited KFRP rupture, in which the optimum joint strength is given with a combination of 80 mm bond length and 4 mm KFRP with joint enhancement of 226.5%, partly due to thicker KFRP plate is more effective at transferring applied stress to neighbouring parts. With respect to volume fraction, 5% eggshell filler is optimum and exceeding 5% prone to exhibit particle agglomerations. Twenty-five 2-D FEA models were developed with apriori two sensitivity studies to ensure strength predictions are independence of mesh refinements and damage stabilization coefficient. Overall, good agreements were seen in both experimental datasets and XFEM models with discrepancies of less than 16.1% (average less than 8%). The FEA modelling techniques are promising for predicting the joint strength of KFRP/steel DSJ.